The influence of the dietary exposome on oxidative stress in pregnancy complications - Prins, Jelmer R. (2022)
Pregnancy complications including fetal growth restriction, preeclampsia, and preterm birth, as well as gestational diabetes, affect one in every four to five pregnancies. Accumulating evidence indicates that increased production of reactive oxygen species accompanies these complications. Given that reactive oxygen species are cell stress-inducing agents, they may have a causal role in disease pathophysiology, although the exact mechanisms by which they contribute to pregnancy complications are not completely understood. Since many environmental and lifestyle factors and exposures are known to modulate reactive oxygen species production, the exposome of pregnant women could contribute to increased generation of reactive oxygen species. The objective of this review is to provide a comprehensive overview of the endogenous and exogenous exposome factors that regulate reactive species in healthy and complicated pregnancies. We also provide a description of dietary interventions aimed at the reduction of reactive species in order to attenuate adverse pregnancy outcome. Dietary interventions in general hold minimal risk in pregnancy and could therefore be considered a promising therapeutic approach.